Healthy lifestyle and atrial fibrillation recurrence after pulmonary vein isolation. (19th May 2022) - Krisai, P; Knecht, S; Badertscher, P; Voellmin, G; Spiess, F; Schaer, B; Osswald, S; Sticherling, C; Kuehne, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Data on the relationship of a healthy lifestyle at the time of atrial fibrillation (AF) ablation with AF recurrence is limited. Purpose: We investigated the association of healthy lifestyle markers with AF recurrence after ablation. Methods: In 1439 patients undergoing AF ablation at a tertiary university hospital, a lifestyle score was built. The score included categories of BMI, smoking, blood pressure, fish intake, fruits/vegetable intake, alcohol consumption and physical activity. A higher score indicated a healthier lifestyle and patients were grouped into tertiles. Follow-up included 24h-Holter ECGs at 3 and 6 months and 7d-Holter ECGs at 12 months. Survival analyses and Cox-regression models were used to assess associations of individual factors and score-tertiles with AF recurrence. Results: Mean age was 61.5 years, 25.9% were female and 59.1% had paroxysmal AF. In 941 patients all lifestyle score variables were available: 129, 675 and 137 patients were in the low, intermediate and high lifestyle group, respectively. Over increasing lifestyle groups, patients were more often female (9.3, 23.3, 38.7%; p<0.0001), had less hypertension (70.5, 53.3, 32.9%; p<0.0001), diabetes (15.5, 6.2, 3.7%; p=0.0002), a smaller left atrial diameter (44.1, 41.0, 37.6mm; p<0.0001) and numerically more paroxysmal AF (56.6, 62.4, 69.4%; p=0.32) with no differences in anti-arrhythmic drugs. In survival analyses (Figure), we saw a trend of more recurrences in the healthiest group compared to the unhealthiest group (logrank p=0.06 for low vs high group). Individually, higher fish intake (logrank p=0.04) and lower blood pressure (logrank p=0.02) were associated with AF recurrence. In Cox-regression models the HR (95% CI) for increasing lifestyle groups was 1.21 (0.98; 1.50, p=0.07). In individual models only higher fish intake (1.25 [1.01; 1.55], p=0.045) was associated with AF recurrence. Conclusion(s): AF recurrence was numerically more frequent in patients with a healthier lifestyle, despite less comorbidities and smaller LA diameters. This paradoxical relationship might be due to lifestyle changes after PVI, differences in PVI efficacy or residual confounding. Further studies are needed to better understand this association.